You are on page 1of 6

MST207 Past Paper 2004

Part 1
Q1 Use separation of variables: dy 1  y2 x 2dx tan-1(y) x3 C 3 x3 tan  3 4
1 2

tan

x3 3

C

When x = 0, y = 1 then tan(C) = 1 and so C = /4 So : y Q2 a

OD

0  (i  0  0)  3

i 2

3 2

j0

3 2

i 3

3 2

i

1 2 3 1 2 2

j
1 2 3 2 2

b
1 2 2

OC 
1 2 3

OD  k 1
1 3 1

1 2 2 3

i

1 2 3

j k
1 2

OC i
1 2 3

OC

j

2 3

c cos()

OC OD

1
3

OC OD

Q3 W = - W j = -mgj T1 = - T1 cos(/4)i + T1 sin(/4)j = -( T1 / 2)i + ( T1 / 2)j T2 = T2 cos(/6)i + T2 sin(/6)j = ( 3 T2 /2)i +( T2 /2)j In equilibrium W + T1 + T2 = 0 Resolving in j-direction: -mgj + ( T1 / 2)j + ( T2 /2)j = 0 So: mg = T1 / 2 + T2 /2 Resolving in i-direction: - T1 / 2 i = gi so T1 = 2 g; -( T1 / 2)i + ( 3 T2 /2)i = 0 So: T1 / 2 = 3 T2 /2 and so T1 = 3 T2 / 2 Substituting: mg = 3 T2 /( 2) + T2 /2 = (1 + 3) T2 So: T2 = 2mg/(1 + 3) as required. Substituting this gives: T1 = ( 6 mg)/(1 + 3) as required. H = -k(x - l0)s = -k(x - l0)i since s = i N= N j W = W sin()i - W cos()j = mg sin()i - mg cos()j x =x i Since we have motion then: mx = H+N+W Resolving in j-direction gives: 0 = N j - W cos()j So: N = W cos() = mg cos() Resolving in i-direction gives: mx i = -k(x - l0)i + mg sin()i mx  = -k(x - l0) + mg sin() So equation of motion is: x  + kx/m = g sin() + kl0/m Equilibrium position, x = leq, is when mass is stationary; i.e. when x  = 0. Substituting gives: leq = (mg sin() + kl0)/k Q4 gx 2 1  tan2 Q5 a Initially  = 0. Since the trajectory is: y h  xtan 2 2u Simplifying gives: 2 2 l g l g y h0 (1  0) or y h 2u 2 2u 2

Since the target is at the same height as the launch then vertical distance that the shot l 2g misses the target is: d 2u 2 b This time the shot is aimed at a height d above the target. So the tangent of the angle of lg Substituting in the trajectory equation gives: projection is: tan 2u 2 y h  l lg 2u 2 gl 2 2u 2 1 lg 2u 2
2

l 4g 3 8u 6

and

l 4g 3 8u 6

C 0

It will only hit the target if the trajectory, y, equals h at l. Since the expression is not zero then the object will fall below the target. We know the expression is not zero since it is composed of all positive elements. Q6 A = 8m; in = 19C; out = 4 C; b = 0.1m; k = 0.6Wm-1K-1; hin = 10Wm-2K-1 hout = 150Wm-2K-1 1 1 1 b q 3.66815 439.02W q   A in out a hin hout k

hinA

in

in

q Ah in

19

439.02 13.5C 108 R1 R2 a R3b R3a 2R2a 2 0 2 1 a 4 0 0 b 2(a 4) 1 2 1

Q7 R1 1 2 1 2 R2 2 2 1 a R3 2 0 b 4

R1 R2a R2 2R1 R3a R3 2R1

2 0 2 1 a 4 0 4 b 2 0 1 2 1

For there to be infinitely many solutions then all the entries on row R3b have to be zero. Hence: b=0 and: -2(a - 4) = 0. So 2a = 8 So: a=4 Q8 a 10 2 0 2 4 11 6 2 2 1 6 1 24 24 12 2 12 2 1 So corresponding eigenvalue is 12.

b Let = 6; (10 - 6)x + 2y + 0 = 2; 4x + (11 - 6)y + 6z = 0; -2x - y + (6 - 6)z = 0 The first and third equations give -2x = y. So if x = 1 the eigenvector so far is [1 -2 z]T Substituting these into equation 2 gives z = 1. So corresponding eigen vector is [1 -2 1]T H lt = -k(x - l0)i H rt = - 2k(d - x - l0)(-i) = 2k(d - x - l0)i R = -rxi mx i = -k(x - l0)i + 2k(d - x - l0)i - rxi which results in: mx + rx + 3kx = k(2d - l0), eqn of motion. Q9 Q10 a By principle of Conservation of momentum: m(ui + vj) + m0 = mpi + mqj. Resolving into i- and j-directions gives p = u and q = v and so after collision one particle has velocity ui and the other vj. b If elastic then K.E. before = K.E. after. K.E. before = mu where u = u = (u + v) so K.E. before = m (u + v). K.E. after = mp + mq where p = p = u and q = q = v so K.E. after = m(u + v). Hence collision is elastic as K.E. before = K.E. after.

Q11 a fx = 8xy + y + 12 fy = 4x + 2xy = x(4x + 2y) Stationary points are found by solving the simultaneous equations fx = and fy = 0. i.e. 8xy + y + 12 = 0 and x(4x + 2y) = 0 The second one gives a solution of x = 0. Substituting this into first equation gives y = -12 which has solutions 2 3i and so (0, +2 3i ) and (0, -2 3i ) are two stationary points. Now: (4x + 2y) = 0 gives: -2x = y. Substituting into fx = 0 gives x = 1. When x = +1, y = -2 and when x = -1, y = +2 (found by substituting values of x into fy = 0 So all stationary points are: (0, +2 3i ); (0, -2 3i ); (1, -2); (-1, 2) b A = fxx = 8y C = fyy = 2x B = fxy = 8x + 2y With point where x is positive: A = fxx(1,-2) = -16; C = fyy(1,-2) = 2; B = fxy(1,-2) = 8 - 4 = 4 AC - B at (1,-2) = 32 + 16 = -16 < 0 hence stationary point is a Saddle Point. Q12 i Plot YN against h4 ii C (Y2 - Y1)/(h14 - h24) = (0.370098 - 0.368018)/((0.25)4 - (0.125)4) 0.568 For 15 d.p. accuracy: h4 < 0.5x10-15/C Thus h < 0.000172 Q13 To find the area we let f, the surface density function, = 1. So: A
x

/2

y cos x

x 0

y 1 2 x/

1 dydx 

y 1 2 x/

/2 y cos x

1 dydx 2

/2

x 0

cos x 1

2x

dx 

/2

2x

cos x dx

sin x x

x2

/2 0

 x

x2

sin x

/2

Q14 Since rotating about fixed axis then K.E = I%2 = 100 J I = Irod + 2Idisk = mrodrrod2 + MdiskRdisk2. So: 100 2 532.765 (1)(0.02)2  3(0.25)2  2 23.08 rad s

Part 2
Q15 i Characteristic equations is: 4 + 4 + 5 = 0 which has solutions - i and so homogeneous solution is: x = e-t(C cos(t) + D sin(t)) Let: xp = ke-t; then: x = -ke-t and: x = ke-t Substituting gives k = 1, so solutions so far is: x = e-t(C cos(t) + D sin(t)) + e-t Let: xp = at + bt + c; then: x = 2at + b; and: x = 2a Substituting gives a = 1, b = 0 and c = 1 so solutions so far is: x = e-t(C cos(t) + D sin(t)) + e-t + t + 1 Since x(0) = 0, substituting gives: 0 = C + 1 + 1 so C = -2. So the solution so far is: x = e-t(D sin(t) - 2cos(t)) + e-t + t + 1 Since x(0) = 0 then x = e-t(Dcos(t) + 2sin(t) - (Dsin(t) - 2cos(t) + 1)) + 2t which, on substitution gives D = -. So the particular solution is: x = e-t(1 - 2cos(t) - sin(t)) + t + 1 Q16 a x =x i; v = vi; N = N j; F = - F i; F = N ; W = - W j = -mgj Since there is motion we have: N + F + W = mx  Resolving in j-direction gives: N = mg. Consequently F = mg Since we have motion then by Newtons Second Law, resolving in idirection gives: mx i = - F i = - mgi. This simplifies to: x =- g vdv 2
2 u0

x v dv g dx Initially when x = 0, v = u0 So:


u0 2
2

g dx 2 v
2 u0

v2 2

gx  C or: x u0 v 2 2 g
2

v2 2

u0 2

g x

2 gx

2 g x

When has come to rest, v = 0. Substituting this, and all the other given values for the 2 constants gives x as: u0 v 2 22 0 x 10.19m (to 2.d.p.) 2 g 20.029.81 b R = - R i = -kvi All other forces and vectors defined as above and F = mg as before. Since there is motion we have: N + F + R + W = mx  Resolving in i-direction now gives: mx i = - F i - R i = - mgi - kvi Hence: x  = - g - kv/m k = c2D = 0.2 x (0.05) = 0.0005 and k/m = 0.0005/2 = 0.00025 = 1/4000 x dv v dx v2 g 4000 vdv g 
v
2

vdv

2000 x  C

2000 4000 g

2000

2vdv 4000 g  v 2

dx

2000 ln 4000 g  v Initially, x = 0 and v = u0. So: c x


2

4000 2

4000

(integrate by substitution)
2

2000 ln 4000 g  u0 so x 2000ln 4000 g  u0


2

2000 ln(4000 g  u0 ) ln(4000 g  v 2)

4000 g  v 2 When comes to rest v = 0. Substituting this and all the other given constants gives: x 2000ln 40000.029.81  22 40000.029.81  0 2000ln(1.0051) 10.17m (to 2.d.p.)

c Adding air resistance stops the mass about 2cm sooner. Two cm over approximately 10.2m represents about 0.2%. So the effect of air resistance accounts for about 0.2% of the resistive force and friction for 99.8% of the resistive force. Air resistance is effectively negligible in this case. Q17 a H1 = -kxi H2 = 4k(y - x)i H3 = - H2 H4 = -kyi mx i = H1 + H2 = -5kxi + 4kyi So: x = k/m(-5x + 4y) Sim: y = k/m(4x - 5y) x y k 5 4 x m 4 5 y

So:

b Eigenvalues of the matrix are -1 and -9 and hence of the whole system are -k/m and -9k/m. The normal mode angular frequencies are given by (- ), where is an eigenvalue of the system. So the normal mode angular frequencies are k/ m and 3 k/ m c Eigenvectors are [1,1] and [-1,1] respectively. Hence general solution is: x(t) 1 1 cos 3 k t  ! C1 cos k t  !  C2 m m 1 y(t) 1 d All phase angles, 3, are zero. At t = 0, then x(0) = 0.1m and y(0) = 0.2m. Substituting gives C1 = 0.15m (15 cm) and C2 = 0.05m (5cm). Hence at time t, the positions x(t) and y(t) are given (in metres) by: 1 x(t) 1 0.15 cos k t  0.05 cos 3 k t m m 1 1 y(t) Q18. This is virtually identical to the 2001 paper Q18 Q 19 a fodd(t) t 0t1 f even(t) t 0t1  t 1t0

( t) 1t0

b Ar c 2 20
1

A0 ( t)cos(r t)dt Br 2

20

( t)dt
2
2 2


t t 2
1 r 2
2 2


1 0

0 (r 1, 2, ...)

20

r 1

cos(r t) 0

(1 cos(r ))


( t)sin(r t)dt

cos(r )


r


(Ar and Br by integration by parts)

d The cosine function would be better because the terms decrease by a factor of 1/r2 compared to the sine function which decreases by a factor of only 1/r each time.

Q 20 a Path is a circle centred on the origin with radius = 1 b r(t) = -sin(t)i + cos(t)j + 0k and F(r) = 2sin(t)i + cos(t)j + sin(t)cos(t)k 2C Fdr 20
2


F(r) r(t) dt

(1

c If the field is conservative then the line integral of any closed loop is zero. The above is a line integral of a closed loop (circle). This is zero when 2 = 1 hence when  = 1. It is not conservative for all other values of . d curl F = (1 - 2)k and so F is conservative only when  = 1.